Scratch-resistant and impact-resistant cover plate glass and preparation method thereof

By coating the cover glass with an aliphatic polyurethane acrylate and modified titanium dioxide, the balance between impact resistance and scratch resistance is solved, the weather resistance and self-cleaning performance are improved, and a combination of high hardness and flexibility is achieved.

CN121610174APending Publication Date: 2026-03-06ZHEJIANG ROCK PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511757038.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-27
Publication Date
2026-03-06

AI Technical Summary

Technical Problem

Existing cover glass struggles to balance impact resistance and scratch resistance, suffers from insufficient long-term weather resistance, is prone to surface contamination and presents cleaning challenges, and has limited wear resistance in existing coatings.

Method used

A surface coating is applied to the glass substrate, using aliphatic polyurethane acrylate as the main film-forming substance, combined with spirocyclic propylene monomers and modified titanium dioxide, and a complementary coating is formed by photocuring to enhance flexibility, adhesion and resistance to yellowing.

Benefits of technology

It achieves a balance between high hardness and flexibility, improves scratch resistance, impact resistance and weather-resistant hydrophobicity, and the coating has excellent self-cleaning properties and long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121610174A_ABST
    Figure CN121610174A_ABST
Patent Text Reader

Abstract

The invention discloses scratch-resistant and impact-resistant cover plate glass and a preparation method thereof, and belongs to the technical field of cover plate glass. The cover plate glass comprises a glass body and a surface coating, wherein the surface coating is prepared from the following components in parts by mass: 20-50 parts of aliphatic polyurethane acrylate, 5-15 parts of a spiro propylene monomer, 2-10 parts of modified titanium dioxide, 60-850 parts of diethyl ether, 30-60 parts of ethanol, 1.5-3 parts of a photoinitiator and 0.2-0.8 part of an auxiliary agent. The spiro propylene monomer is prepared through a reaction containing a spiro ring and a phenyl ether structure, and the balance of rigidity and flexibility is enhanced; acryloyl and fluorophosphonyl are grafted on the surface of the modified titanium dioxide, so that the dispersity, the crosslinking density and the hydrophobicity are improved. The preparation method comprises the following steps: coating a glass body with a coating solution, pre-curing, and then carrying out ultraviolet curing. Through the synergistic effect of the coating components, the cover plate glass has excellent impact resistance, scratch resistance, weather resistance and hydrophobicity, and the problems of insufficient performance balance and durability in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cover glass technology, and particularly relates to a scratch-resistant and impact-resistant cover glass and its preparation method. Background Technology

[0002] Cover glass, a type of special glass widely used in electronic display devices, instruments, automotive center consoles, and building curtain walls, is a transparent protective material covering the outermost layer of a display screen or touchscreen. It not only bears the core responsibility of protecting internal precision components (such as LCD modules, touch sensors, and OLEDs) from external mechanical damage and environmental corrosion, but also directly determines the visual appeal, touch experience, and durability of the final product. With the rapid development of the electronics and information industry, from smartphones and tablets to wearable devices, in-vehicle screens, and public information query systems, cover glass has become an indispensable key component of modern smart devices. Its performance directly affects the product's market competitiveness and the user's lifespan.

[0003] Early cover glass primarily used ordinary soda-lime glass, but it had low hardness, was easily scratched, and had poor impact resistance. Subsequently, high-alumina silicate glass, through ion exchange technology, formed a compressive stress layer on the glass surface, significantly improving its impact and scratch resistance, and became the mainstream in the market. Meanwhile, transparent microcrystalline glass, through controlled crystallization to form nanoscale microcrystalline phases, achieved higher hardness and superior drop resistance, representing a high-end trend. In addition to strengthening the glass itself, surface functional coating technologies are also widely used, such as depositing anti-reflective (AR) films, anti-fingerprint (AF) films, and anti-static (AS) films on the glass surface to endow it with more functional properties.

[0004] Despite significant advancements in existing technology, cover glass still faces numerous challenges and unresolved issues in practical applications. Firstly, balancing impact resistance and scratch resistance remains a technical hurdle. While chemically strengthened glass boasts high surface hardness and scratch resistance, it remains inherently brittle, prone to radial or spiderweb-like cracks, or even complete rupture, when subjected to sharp objects or high-energy impacts. Conversely, some polymer coatings designed to enhance toughness often lack sufficient hardness, making them ill-suited to resist scratches from everyday objects like keys and grit. Secondly, long-term weather resistance and stability are insufficient. Prolonged exposure to ultraviolet radiation, moisture, and temperature fluctuations can cause some organic coatings to yellow, chalk, and lose adhesion, leading to deterioration in optical performance and failure of protective functions. Furthermore, surface contamination and cleaning difficulties also negatively impact user experience. Fingerprints and oil stains easily adhere, affecting aesthetics and touch sensitivity, while existing oleophobic coatings lack sufficient abrasion resistance and have limited lifespan. Therefore, there is an urgent need in this field for a cover glass solution with superior overall performance. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention applies a surface coating to the glass body. The surface coating uses aliphatic polyurethane acrylate as the main film-forming substance, which provides good flexibility, adhesion and yellowing resistance. It complements the spirocyclic monomer and modified titanium dioxide, further optimizing the mechanical properties of the coating. As a result, the cover glass has excellent impact resistance, scratch resistance and weather-resistant hydrophobicity.

[0006] To achieve the above objectives, the following technical solution is adopted: This invention provides a scratch-resistant and impact-resistant cover glass, comprising a glass body and a surface coating; the surface coating comprises the following components in parts by weight: 20-50 parts aliphatic polyurethane acrylate, 5-15 parts spirocyclic propylene monomer, 2-10 parts modified titanium dioxide, 60-850 parts diethyl ether, 30-60 parts ethanol, 1.5-3 parts photoinitiator, and 0.2-0.8 parts additives.

[0007] Furthermore, the modified titanium dioxide is prepared through the following steps: S1. Dissolve tetrabutyl titanate in anhydrous ethanol and stir to form a homogeneous solution. Slowly add glacial acetic acid, then add 0.3%-0.6% nitric acid solution. Continue stirring for 2-3.5 hours after the addition is complete. Transfer the formed sol to a polytetrafluoroethylene container and age it at 60-70℃ for 48-60 hours. Then dry it in a forced-air drying oven at 90-100℃ for 16-20 hours to obtain a dry gel. Place the dry gel in a muffle furnace and heat it to 500-600℃ at a rate of 5-8℃ / min. Calcinate it at this temperature for 2.5-3 hours. After naturally cooling to room temperature, grind it and pass it through a 300-mesh sieve to obtain nano-titanium dioxide powder. S2. Add bis(2,2,2-trifluoroethyl) phosphonate to anhydrous acetonitrile, then add anhydrous potassium carbonate and potassium iodide, and activate under nitrogen protection at 30-40℃ for 20-30 min by stirring. Then slowly add 2-bromoethyl acrylate dropwise. After the addition is complete, raise the temperature to 65-75℃ and stir at 250-300 rpm for 6-8 h. After the reaction is complete, cool to room temperature, filter, and remove the solvent from the filtrate by vacuum distillation. Recrystallize the crude product three times with a 1:3 volume ratio of ethyl acetate-n-hexane mixed solvent, and dry under vacuum to obtain the modified intermediate. S3. Add nano-titanium dioxide to anhydrous isopropanol and ultrasonically disperse it for 40-60 min at a power of 300-400W until a uniform suspension is formed. Add the modified intermediate and γ-(methacryloyloxy)propyltrimethoxysilane to the suspension and stir the mixture at 55-65℃ and 200-250 rpm for 4-5 h under a nitrogen atmosphere. After the reaction is completed, centrifuge the mixture at 8000-10000 rpm for 15-20 min, collect the solid precipitate, wash it three times with anhydrous ethanol, vacuum dry it, and grind it through a 400-mesh sieve to obtain modified titanium dioxide powder with acryloyl and fluorophosphonoyl groups grafted on its surface.

[0008] Further, the spirocyclic propylene monomer is prepared by the following steps: (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid is dissolved in anhydrous toluene, triethylamine and tetrabutylammonium bromide are added, and 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide is slowly added under nitrogen protection, at 50-60℃ and 300-400 rpm. After the addition is complete, the temperature is raised to 70-80℃ and reacted for 6-8 hours. After the reaction solution is cooled, water is added and the mixture is allowed to stand and separate into layers. The organic phase is washed with 5% dilute hydrochloric acid and deionized water until neutral, dried with anhydrous sodium sulfate, filtered, and the solvent is removed under reduced pressure to obtain the spirocyclic propylene monomer.

[0009] Furthermore, the feeding ratio of tetrabutyl titanate, anhydrous ethanol, glacial acetic acid and nitric acid solution is 30-50g: 30-75mL: 2.5-6.5mL: 1-2.5mL.

[0010] Further, the feeding ratio of bis(2,2,2-trifluoroethyl) phosphonate, 2-bromoethyl acrylate, and anhydrous acetonitrile is 20-50g: 15-41g: 140-600mL, the feeding amount of anhydrous potassium carbonate is 5%-8% of the molar amount of bis(2,2,2-trifluoroethyl) phosphonate, and the feeding amount of potassium iodide is 2%-3% of the mass of bis(2,2,2-trifluoroethyl) phosphonate.

[0011] Furthermore, the feeding ratio of the nano-titanium dioxide, anhydrous isopropanol, and 2-(acryloyloxy)ethylphosphonic acid bis(2,2,2-trifluoroethyl) ester is 10-20g: 127-382mL: 0.8-2.4g, and the feeding amount of γ-(methacryloyloxy)propyltrimethoxysilane is 0.5%-0.8% of the mass of the nano-titanium dioxide.

[0012] Further, the feeding ratio of (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid, 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide and anhydrous toluene is 20-50g: 35-92g: 150-200mL, the feeding amount of triethylamine is 3%-5% of the molar amount of (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid, and the feeding amount of tetrabutylammonium bromide is 0.8%-1.2% of the total mass of the reactants.

[0013] Furthermore, the weight-average molecular weight of the aliphatic polyurethane acrylate is 1000-15000 g / mol.

[0014] Furthermore, the photoinitiator is selected from at least one of benzoyl peroxide, dicumyl peroxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 1-hydroxycyclohexylphenyl ketone.

[0015] Furthermore, the additive is selected from at least one of BYK-3455, BYK-3550, BYK052N, BYK-061, and BYK-065.

[0016] On the other hand, the present invention also provides a method for preparing the scratch-resistant and impact-resistant cover glass, comprising the following steps: (1) Mix aliphatic polyurethane acrylate, spirocyclic propylene monomer, modified titanium dioxide, diethyl ether, ethanol, photoinitiator and additives according to the mass parts, and mechanically stir at a speed of 300-500 rpm for 30-60 min under light-protected conditions to obtain a uniform and transparent coating solution. (2) The layer solution is coated onto the clean glass body surface by spin coating or slit coating, with a coating thickness of 10-50 μm, and then left to stand in an oven at 40-60℃ for 3-5 min to evaporate some of the solvent. (3) Transfer the glass body pre-cured in step (2) to an ultraviolet curing device, and under a nitrogen protective atmosphere, use a wavelength of 365nm and a light intensity of 800-1200mW / cm². 2 Irradiate with ultraviolet light for 10-30 seconds to allow the surface coating to fully cross-link and cure, thus obtaining the scratch-resistant and impact-resistant cover glass.

[0017] The beneficial effects of this invention are: By applying a surface coating to the glass body, the surface coating uses aliphatic polyurethane acrylate as the main film-forming substance, providing good flexibility, adhesion and yellowing resistance. It complements the spirocyclic monomer and modified titanium dioxide, further optimizing the mechanical properties of the coating, so that the resulting cover glass ultimately has excellent impact resistance, scratch resistance and weather-resistant hydrophobicity.

[0018] The spirocyclic propylene monomer is prepared by reacting (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid with 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide. The hydroxyl groups generated during the reaction can act as chain extenders and participate in the cross-linking reaction during photocuring to enhance the connection between molecular chains. The monomer molecule contains both a rigid tetraoxaspirocyclic structure and a flexible phenyl ether structure. The highly symmetrical and stable ring configuration of the rigid spirocyclic structure can effectively restrict the movement of molecular chain segments, increase the rigidity and modulus of the coating, and thus significantly improve scratch resistance and surface hardness. The ether bond gives the molecular chain good rotational ability and flexibility, which can absorb and disperse external impact energy and avoid stress concentration, thereby improving the toughness and impact resistance of the coating, so that the coating can maintain high hardness while also having excellent flexibility. The surface of modified titanium dioxide was grafted with bis(2,2,2-trifluoroethyl) 2-(acryloyloxy)ethylphosphonic acid and γ-(methacryloyloxy)propyltrimethoxysilane. The phosphonate groups on the surface of the nano-titanium dioxide formed stable Ti-OP covalent bonds with the titanium atoms. Simultaneously, the silane coupling agent reacted with the hydroxyl groups on the titanium dioxide surface through hydrolysis and condensation. The synergistic effect of these two factors significantly improved the dispersibility and interfacial compatibility of the nanoparticles in the resin matrix, preventing agglomeration and ensuring uniform distribution of the nanoparticles, thus fully leveraging their reinforcing effect. The grafted acryloyl and fluorophosphonoyl groups... The double bonds can participate in photo-initiated cross-linking reactions, covalently bonding titanium dioxide nanoparticles to the polymer network. As cross-linking points, they increase the cross-linking density of the three-dimensional network, making the coating structure more compact and effectively improving hardness, wear resistance, and scratch resistance. The trifluoroethyl groups introduced through bis(2,2,2-trifluoroethyl) ester have extremely low surface energy and strong hydrophobicity, which can significantly reduce the surface tension of the coating, giving it excellent hydrophobic, anti-fouling, and self-cleaning properties. At the same time, it makes the coating more stable to ultraviolet rays, high temperatures, and oxidizing environments, thereby enhancing weather resistance and durability. Attached Figure Description

[0019] Figure 1 The equations for the preparation process of the modified intermediate and spirocyclic propylene monomer in this invention are as follows; Figure 2 Modified intermediates prepared for this invention 1 HNMR spectrum; Figure 3 Spirocyclic propylene monomer prepared according to the present invention 1 HNMR spectrum.

[0020] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.

[0023] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the experimental materials used in the following examples are all purchased from commercial channels. Figure 1 The figure shows the preparation process equations for the modified intermediate and spirocyclic propylene monomer in this invention.

[0024] Example 1:

[0025] A scratch-resistant and impact-resistant cover glass includes a glass body and a surface coating; the surface coating comprises the following components in parts by weight: 20 parts aliphatic polyurethane acrylate, 5 parts spirocyclic propylene monomer, 2 parts modified titanium dioxide, 60 parts diethyl ether, 30 parts ethanol, 1.5 parts photoinitiator, and 0.2 parts additives.

[0026] The modified titanium dioxide is prepared through the following steps: S1. Tetrabutyl titanate was dissolved in anhydrous ethanol and stirred to form a homogeneous solution. Glacial acetic acid was slowly added dropwise, followed by 0.3% nitric acid solution. After the addition was complete, stirring was continued for 2 hours. The resulting sol was transferred to a polytetrafluoroethylene container and aged at 60°C for 48 hours. Then, it was dried in a 90°C forced-air drying oven for 16 hours to obtain a dry gel. The dry gel was placed in a muffle furnace and heated to 500°C at a rate of 5°C / min. It was calcined at this temperature for 2.5 hours. After naturally cooling to room temperature, it was ground and passed through a 300-mesh sieve to obtain nano-titanium dioxide powder. S2. Bis(2,2,2-trifluoroethyl) phosphonate was added to anhydrous acetonitrile, followed by anhydrous potassium carbonate and potassium iodide. The mixture was stirred and activated at 30°C for 20 min under nitrogen protection. Then, 2-bromoethyl acrylate was slowly added dropwise. After the addition was complete, the temperature was raised to 65°C and the mixture was stirred at 250 rpm for 6 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The solvent in the filtrate was removed by vacuum distillation. The crude product was recrystallized three times with a 1:3 volume ratio of ethyl acetate to n-hexane mixed solvent. After vacuum drying, the modified intermediate was obtained. S3. Add nano-titanium dioxide to anhydrous isopropanol and ultrasonically disperse it for 40 min at 300 W to form a uniform suspension. Add the modified intermediate and γ-(methacryloyloxy)propyltrimethoxysilane to the suspension and stir at 55 °C and 200 rpm for 4 h under a nitrogen atmosphere. After the reaction is completed, centrifuge the mixture at 8000 rpm for 15 min, collect the solid precipitate, wash it three times with anhydrous ethanol, vacuum dry it, grind it through a 400 mesh sieve to obtain modified titanium dioxide powder with acryloyl and fluorophosphonoyl groups grafted on the surface.

[0027] The spirocyclic propylene monomer was prepared by the following steps: (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid was dissolved in anhydrous toluene, triethylamine and tetrabutylammonium bromide were added, and 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide was slowly added under nitrogen protection, at 50°C and 300 rpm. After the addition was complete, the temperature was raised to 70°C and reacted for 6 h. After the reaction solution was cooled, water was added and the mixture was allowed to stand and separate into layers. The organic phase was washed with 5% dilute hydrochloric acid and deionized water until neutral, dried with anhydrous sodium sulfate, filtered, and the solvent was removed under reduced pressure to obtain the spirocyclic propylene monomer.

[0028] The feeding ratio of tetrabutyl titanate, anhydrous ethanol, glacial acetic acid and nitric acid solution is 30g:30mL:2.5mL:1mL.

[0029] The feeding ratio of bis(2,2,2-trifluoroethyl) phosphonate, 2-bromoethyl acrylate, and anhydrous acetonitrile is 20g:15g:140mL. The amount of anhydrous potassium carbonate fed is 5% of the molar amount of bis(2,2,2-trifluoroethyl) phosphonate, and the amount of potassium iodide fed is 2% of the mass of bis(2,2,2-trifluoroethyl) phosphonate.

[0030] The feeding ratio of nano-titanium dioxide, anhydrous isopropanol, and 2-(acryloyloxy)ethylphosphonic acid bis(2,2,2-trifluoroethyl) ester is 10g:127mL:0.8g, and the feeding amount of γ-(methacryloyloxy)propyltrimethoxysilane is 0.5% of the mass of nano-titanium dioxide.

[0031] The feed ratio of (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid, 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide and anhydrous toluene is 20g:35g:150mL. The amount of triethylamine fed is 3% of the molar amount of (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid. The amount of tetrabutylammonium bromide fed is 0.8% of the total mass of the reactants.

[0032] The aliphatic polyurethane acrylate has a weight-average molecular weight of 1000 g / mol; the photoinitiator is benzoyl peroxide; and the additive is BYK-3455.

[0033] A method for preparing the scratch-resistant and impact-resistant cover glass includes the following steps: (1) Mix aliphatic polyurethane acrylate, spirocyclic propylene monomer, modified titanium dioxide, diethyl ether, ethanol, photoinitiator and additives according to the mass parts, and mechanically stir at 300 rpm for 30 min under light-protected conditions to obtain a uniform and transparent coating solution. (2) The layer solution is coated onto the clean glass body surface by spin coating or slit coating, with a coating thickness of 10 μm, and then left to stand in an oven at 40°C for 3 min to evaporate some of the solvent. (3) Transfer the glass body pre-cured in step (2) to an ultraviolet curing device, and use a wavelength of 365nm and a light intensity of 800mW / cm² under a nitrogen protective atmosphere. 2 Irradiate with ultraviolet light for 10 seconds to allow the surface coating to fully cross-link and cure, thus obtaining the scratch-resistant and impact-resistant cover glass.

[0034] Example 2:

[0035] A scratch-resistant and impact-resistant cover glass includes a glass body and a surface coating; the surface coating comprises the following components in parts by weight: 50 parts aliphatic polyurethane acrylate, 15 parts spirocyclic propylene monomer, 10 parts modified titanium dioxide, 850 parts diethyl ether, 60 parts ethanol, 3 parts photoinitiator, and 0.8 parts additives.

[0036] The modified titanium dioxide is prepared through the following steps: S1. Tetrabutyl titanate was dissolved in anhydrous ethanol and stirred to form a homogeneous solution. Glacial acetic acid was slowly added dropwise, followed by 0.6% nitric acid solution. After the addition was complete, stirring was continued for 3.5 hours. The resulting sol was transferred to a polytetrafluoroethylene container and aged at 70°C for 60 hours. Then, it was dried in a 100°C forced-air drying oven for 20 hours to obtain a dry gel. The dry gel was placed in a muffle furnace and heated to 600°C at a rate of 8°C / min. It was calcined at this temperature for 3 hours. After naturally cooling to room temperature, it was ground and passed through a 300-mesh sieve to obtain nano-titanium dioxide powder. S2. Bis(2,2,2-trifluoroethyl) phosphonate was added to anhydrous acetonitrile, followed by anhydrous potassium carbonate and potassium iodide. The mixture was stirred and activated at 40°C for 30 min under nitrogen protection. Then, 2-bromoethyl acrylate was slowly added dropwise. After the addition was complete, the temperature was raised to 75°C and the mixture was stirred at 300 rpm for 8 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The filtrate was distilled under reduced pressure to remove the solvent. The crude product was recrystallized three times with a 1:3 volume ratio of ethyl acetate to n-hexane mixed solvent. After vacuum drying, the modified intermediate was obtained. S3. Add nano-titanium dioxide to anhydrous isopropanol and ultrasonically disperse it for 60 min at 400 W to form a uniform suspension. Add the modified intermediate and γ-(methacryloyloxy)propyltrimethoxysilane to the suspension and stir at 65 °C and 250 rpm for 5 h under a nitrogen atmosphere. After the reaction is completed, centrifuge the mixture at 10000 rpm for 20 min, collect the solid precipitate, wash it three times with anhydrous ethanol, vacuum dry it, and grind it through a 400-mesh sieve to obtain modified titanium dioxide powder with acryloyl and fluorophosphonoyl groups grafted on the surface.

[0037] The spirocyclic propylene monomer was prepared by the following steps: (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid was dissolved in anhydrous toluene, triethylamine and tetrabutylammonium bromide were added, and 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide was slowly added under nitrogen protection, at 60°C and 400 rpm. After the addition was complete, the temperature was raised to 80°C and reacted for 8 hours. After the reaction solution was cooled, water was added and the mixture was allowed to stand and separate into layers. The organic phase was washed with 5% dilute hydrochloric acid and deionized water until neutral, dried with anhydrous sodium sulfate, filtered, and the solvent was removed under reduced pressure to obtain the spirocyclic propylene monomer.

[0038] The feeding ratio of tetrabutyl titanate, anhydrous ethanol, glacial acetic acid and nitric acid solution is 50g:75mL:6.5mL:2.5mL.

[0039] The feeding ratio of bis(2,2,2-trifluoroethyl) phosphonate, 2-bromoethyl acrylate, and anhydrous acetonitrile is 50g:41g:600mL. The amount of anhydrous potassium carbonate fed is 8% of the molar amount of bis(2,2,2-trifluoroethyl) phosphonate, and the amount of potassium iodide fed is 3% of the mass of bis(2,2,2-trifluoroethyl) phosphonate.

[0040] The feeding ratio of nano-titanium dioxide, anhydrous isopropanol, and 2-(acryloyloxy)ethylphosphonic acid bis(2,2,2-trifluoroethyl) ester is 20g:382mL:2.4g, and the feeding amount of γ-(methacryloyloxy)propyltrimethoxysilane is 0.8% of the mass of nano-titanium dioxide.

[0041] The feed ratio of (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid, 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide and anhydrous toluene is 50g:92g:200mL, the feed amount of triethylamine is 5% of the molar amount of (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid, and the feed amount of tetrabutylammonium bromide is 1.2% of the total mass of the reactants.

[0042] The aliphatic polyurethane acrylate has a weight-average molecular weight of 15000 g / mol; the photoinitiator is dicumyl peroxide; and the additive is BYK-3550.

[0043] A method for preparing the scratch-resistant and impact-resistant cover glass includes the following steps: (1) Mix aliphatic polyurethane acrylate, spirocyclic propylene monomer, modified titanium dioxide, diethyl ether, ethanol, photoinitiator and additives according to the mass parts, and mechanically stir at 500 rpm for 60 min under light-protected conditions to obtain a uniform and transparent coating solution. (2) The layer solution is coated onto the clean glass body surface by spin coating or slit coating, with a coating thickness of 50 μm, and then left to stand in an oven at 60°C for 5 min to evaporate some of the solvent. (3) Transfer the glass body pre-cured in step (2) to an ultraviolet curing device, and under a nitrogen protective atmosphere, use a wavelength of 365nm and a light intensity of 1200mW / cm². 2 The surface coating is completely cross-linked and cured by irradiation with ultraviolet light for 30 seconds, thus obtaining the scratch-resistant and impact-resistant cover glass.

[0044] Example 3:

[0045] A scratch-resistant and impact-resistant cover glass includes a glass body and a surface coating; the surface coating comprises the following components in parts by weight: 35 parts aliphatic polyurethane acrylate, 10 parts spirocyclic propylene monomer, 6 parts modified titanium dioxide, 455 parts diethyl ether, 45 parts ethanol, 2.2 parts photoinitiator, and 0.5 parts additives.

[0046] The modified titanium dioxide is prepared through the following steps: S1. Tetrabutyl titanate was dissolved in anhydrous ethanol and stirred to form a homogeneous solution. Glacial acetic acid was slowly added dropwise, followed by 0.45% nitric acid solution. After the addition was complete, stirring was continued for 2.8 hours. The resulting sol was transferred to a polytetrafluoroethylene container and aged at 65°C for 54 hours. Then, it was dried in a 95°C forced-air drying oven for 18 hours to obtain a dry gel. The dry gel was placed in a muffle furnace and heated to 550°C at a rate of 6.5°C / min. It was calcined at this temperature for 2.8 hours. After naturally cooling to room temperature, it was ground and passed through a 300-mesh sieve to obtain nano-titanium dioxide powder. S2. Bis(2,2,2-trifluoroethyl) phosphonate was added to anhydrous acetonitrile, followed by anhydrous potassium carbonate and potassium iodide. The mixture was stirred and activated at 35°C for 25 min under nitrogen protection. Then, 2-bromoethyl acrylate was slowly added dropwise. After the addition was complete, the temperature was raised to 70°C and the mixture was stirred at 275 rpm for 7 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the solvent was removed by vacuum distillation of the filtrate. The crude product was recrystallized three times with a 1:3 volume ratio of ethyl acetate-n-hexane mixed solvent. After vacuum drying, the modified intermediate was obtained. S3. Add nano-titanium dioxide to anhydrous isopropanol and ultrasonically disperse it for 50 min at 350 W to form a uniform suspension. Add the modified intermediate and γ-(methacryloyloxy)propyltrimethoxysilane to the suspension and stir at 60 °C and 225 rpm for 4.5 h under a nitrogen atmosphere. After the reaction is completed, centrifuge the mixture at 9000 rpm for 17.5 min, collect the solid precipitate, wash it three times with anhydrous ethanol, vacuum dry it, and grind it through a 400-mesh sieve to obtain modified titanium dioxide powder with acryloyl and fluorophosphonoyl groups grafted on the surface.

[0047] The spirocyclic propylene monomer was prepared by the following steps: (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid was dissolved in anhydrous toluene, triethylamine and tetrabutylammonium bromide were added, and 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide was slowly added under nitrogen protection, at 55°C and 350 rpm stirring. After the addition was complete, the temperature was raised to 75°C and reacted for 7 h. After the reaction solution was cooled, water was added and the mixture was allowed to stand and separate into layers. The organic phase was washed with 5% dilute hydrochloric acid and deionized water until neutral, dried with anhydrous sodium sulfate, filtered, and the solvent was removed under reduced pressure to obtain the spirocyclic propylene monomer.

[0048] The feeding ratio of tetrabutyl titanate, anhydrous ethanol, glacial acetic acid and nitric acid solution is 40g:52.5mL:4.5mL:1.75mL.

[0049] The feeding ratio of bis(2,2,2-trifluoroethyl) phosphonate, 2-bromoethyl acrylate, and anhydrous acetonitrile is 35g:28g:370mL. The amount of anhydrous potassium carbonate fed is 6.5% of the molar amount of bis(2,2,2-trifluoroethyl) phosphonate, and the amount of potassium iodide fed is 2.5% of the mass of bis(2,2,2-trifluoroethyl) phosphonate.

[0050] The feeding ratio of nano-titanium dioxide, anhydrous isopropanol, and 2-(acryloyloxy)ethylphosphonic acid bis(2,2,2-trifluoroethyl) ester is 15g:254.5mL:1.6g, and the feeding amount of γ-(methacryloyloxy)propyltrimethoxysilane is 0.65% of the mass of nano-titanium dioxide.

[0051] The feed ratio of (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid, 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide and anhydrous toluene is 35g:63.5g:175mL. The feed amount of triethylamine is 4% of the molar amount of (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid. The feed amount of tetrabutylammonium bromide is 1.0% of the total mass of the reactants.

[0052] The aliphatic polyurethane acrylate has a weight-average molecular weight of 8000 g / mol; the photoinitiator is a mixture of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-hydroxycyclohexylphenyl methyl ketone in a mass ratio of 1:1; the additive is a mixture of BYK052N and BYK-061 in a mass ratio of 1:1.

[0053] A method for preparing the scratch-resistant and impact-resistant cover glass includes the following steps: (1) Mix aliphatic polyurethane acrylate, spirocyclic propylene monomer, modified titanium dioxide, diethyl ether, ethanol, photoinitiator and additives according to the mass parts, and mechanically stir at 400 rpm for 45 min under light-protected conditions to obtain a uniform and transparent coating solution. (2) The layer solution is coated onto the clean glass body surface by spin coating or slit coating, with a coating thickness of 30 μm, and then left to stand in an oven at 50 °C for 4 min to evaporate some of the solvent. (3) Transfer the glass body pre-cured in step (2) to an ultraviolet curing device, and under a nitrogen protective atmosphere, use a wavelength of 365nm and a light intensity of 1000mW / cm². 2 Irradiate with ultraviolet light for 20 seconds to allow the surface coating to fully cross-link and cure, thus obtaining the scratch-resistant and impact-resistant cover glass.

[0054] Example 4:

[0055] In this embodiment, the photoinitiator is a mixture of benzoyl peroxide and 1-hydroxycyclohexylphenyl ketone in a mass ratio of 1:1:1; the auxiliary agent is a mixture of BYK-3455, BYK-3550, BYK-061, and BYK-065 in a mass ratio of 1:1:1:1.

[0056] Comparative Example 1: In this comparative example, no spirocyclic propylene monomer was added to the surface coating, and the other components and preparation process were the same as in Example 3.

[0057] Comparative Example 2: In this comparative example, no modified titanium dioxide was added to the surface coating; all other components and preparation processes were the same as in Example 3. Comparative Example 3: The surface coating in this comparative example uses ordinary nano-titanium dioxide powder without modification, and the other components are the same as in Example 3.

[0058] Comparative Example 4: In the surface coating, ordinary acrylate monomers are used instead of spirocyclic propylene monomers, that is, an equal amount of ethoxylated pentaerythritol tetraacrylate is used instead of spirocyclic propylene monomers, and other components are the same as in Example 3.

[0059] Results Analysis The modified intermediate and spirocyclic propylene monomer prepared in this invention were characterized by nuclear magnetic resonance (NMR), and their images are shown below. Figure 2 and Figure 3 . Figure 2 The multiple peak at 2.08 ppm is a characteristic peak of hydrogen on the methylene group connected to the phosphorus atom. It has a low chemical shift value and is obviously affected by the phosphorus-oxygen bond, indicating that the modified intermediate was successfully synthesized by reacting bis(2,2,2-trifluoroethyl) phosphonate with 2-bromoethyl acrylate. Figure 3 The singlet at 5.25 ppm is a characteristic peak of hydrogen on the hydroxyl group, while the multiplet at 7.29 ppm is a characteristic peak of hydrogen on the methylene group connected to the hydroxyl group. This proves that (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid and 2-[[4-(2-propen-1-oxy)phenoxy]methyl]-ethylene oxide were successfully reacted to synthesize a spirocyclic propylene monomer.

[0060] The cover glass prepared in Examples 1-4 and Comparative Examples 1-4 of the present invention was subjected to the following tests, and the test results are shown in Table 1: Pencil hardness test: According to GB / T 6739-2006 standard, the surface hardness of the coating is tested using a pencil hardness tester, ranging from 6B to 9H. The higher the hardness value, the better the scratch resistance.

[0061] Drop ball impact test: According to GB / T 2423.55-2006 standard, a steel ball (50mm in diameter, 500g in mass) is dropped freely from different heights to impact the center of the glass. The maximum impact height (unit: cm) without the glass breaking is recorded. The higher the value, the better the impact resistance.

[0062] Contact angle test: The contact angle between the coating surface and water is measured using a contact angle meter. The larger the value, the better the hydrophobicity.

[0063] UV aging test: According to GB / T 14522-2008 standard, the sample was placed in a UV aging chamber (wavelength 340nm, irradiance 0.76W / m²). 2 After continuous irradiation at 60℃ for 500 hours, the pencil hardness retention rate (%) was measured.

[0064] Abrasion resistance test: According to GB / T 1768-2006 standard, the coating surface is rubbed 1000 times with a rubber grinding wheel (500g load), and the change in haze before and after friction is measured. The smaller the value, the better the abrasion resistance.

[0065] Table 1. Comparison of test results for cover glass in each embodiment and comparative example.

[0066] Figure 1 In the examples, all samples achieved 8H, indicating that the coating has extremely high surface hardness and scratch resistance, mainly attributed to the rigid spirocyclic structure of the spirocyclic propylene monomer and the high crosslinking density of the modified titanium dioxide. The comparative examples, lacking these key components, showed a significant decrease in hardness. The impact height of all examples exceeded 50 cm, demonstrating excellent impact resistance. This is due to the combined effect of the flexible ether bonds of the spirocyclic monomer and the flexibility of the polyurethane acrylate, which effectively absorbs impact energy. Comparative Examples 1 and 4, lacking the spirocyclic structure, exhibited the worst impact resistance. The contact angle of all examples was greater than 105°, indicating excellent hydrophobicity of the coating, mainly due to the low surface energy of the trifluoroethyl groups grafted onto the modified titanium dioxide surface. After UV aging, the retention rate of all examples was higher than 95%, indicating good weather resistance of the coating. The stability of the fluorophosphonoyl group and spirocyclic structure of the modified titanium dioxide played a crucial role. In the abrasion resistance test, the haze change of all examples was less than or equal to 3%, indicating excellent abrasion resistance of the coating.

[0067] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0068] The present invention and its embodiments have been described above. This description is not restrictive, and the embodiments shown are only one of the embodiments of the present invention. The actual application is not limited to this. In conclusion, if those skilled in the art are inspired by this description and design similar methods and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. An anti-scratch, impact-resistant cover glass, characterized by: The glass body and the surface coating layer; the surface coating layer comprises the following components by mass fraction: 20-50 parts of aliphatic polyurethane acrylate, 5-15 parts of spirocyclic acrylate monomer, 2-10 parts of modified titanium dioxide, 60-850 parts of diethyl ether, 30-60 parts of ethanol, 1.5-3 parts of photoinitiator, 0.2-0.8 parts of auxiliary agent; The modified titanium dioxide is prepared by the following steps: S1. Dissolve tetrabutyl titanate in anhydrous ethanol to form a uniform solution, slowly drop acetic acid, then drop 0.3%-0.6% mass fraction of nitric acid solution, continue stirring for 2-3.5h after dropping, transfer the formed sol to a polytetrafluoroethylene container, stand at 60-70℃ for 48-60h, then dry in a 90-100℃ air-drying oven for 16-20h to obtain a dry gel; place the dry gel in a muffle furnace, heat to 500-600℃ at a rate of 5-8℃ / min, keep the temperature for 2.5-3h, naturally cool to room temperature, grind and pass through a 300 mesh sieve to obtain nano titanium dioxide powder; S2. Add bis(2,2,2-trifluoroethyl) phosphonate to anhydrous acetonitrile, then add anhydrous potassium carbonate and potassium iodide, stir at 30-40℃ for 20-30min under nitrogen protection; then slowly drop 2-bromoethyl acrylate, heat to 65-75℃ after dropping, stir at 250-300rpm for 6-8h, after the reaction is completed, cool to room temperature, filter, remove the solvent from the filtrate by reduced pressure distillation, recrystallize the crude product with a volume ratio of 1:3 of ethyl acetate-n-hexane mixed solvent for 3 times, and vacuum dry to obtain a modified intermediate; S3. Add nano titanium dioxide to anhydrous isopropyl alcohol, ultrasonic dispersion for 40-60min under a power of 300-400W to form a uniform suspension; Add the modified intermediate and γ-(methacryloyloxy)propyltrimethoxysilane to the suspension, stir at 200-250rpm at 55-65℃ under nitrogen atmosphere for 4-5h; after the reaction is completed, centrifuge the mixture at 8000-10000rpm for 15-20min, collect the solid precipitate, wash with anhydrous ethanol for 3 times, vacuum dry, grind and pass through a 400 mesh sieve to obtain modified titanium dioxide powder with acryloyl and fluorophosphoryl groups grafted on the surface.

2. The scratch-resistant impact-resistant cover glass according to claim 1, wherein: The spirocyclic acrylate monomer is prepared by the following steps: dissolve (9CI)-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dipropionic acid in anhydrous toluene, add triethylamine and tetrabutylammonium bromide, slowly add 2-[[4-(2-propen-1-oxyl)phenoxy]methyl]oxirane under nitrogen protection, stirring at 300-400rpm at 50-60℃, heat to 70-80℃ after dropping, react for 6-8h, after the reaction solution is cooled, add water and stand to separate into layers, wash the organic phase with 5% dilute hydrochloric acid and deionized water until neutral, add anhydrous sodium sulfate, dry and filter, remove the solvent under reduced pressure to obtain the spirocyclic acrylate monomer.

3. The scratch resistant impact resistant cover glass according to claim 2, wherein: The feeding ratio of the tetrabutyl titanate, absolute ethanol, glacial acetic acid and nitric acid solution is 30-50 g: 30-75 mL: 2.5-6.5 mL: 1-2.5 mL.

4. The scratch and impact resistant cover glass of claim 2, wherein: The feeding ratio of the phosphonic acid bis (2, 2, 2-trifluoroethyl) ester, 2-bromoethyl acrylate, absolute acetonitrile is 20-50 g: 15-41 g: 140-600 mL, the feeding amount of the absolute potassium carbonate is 5%-8% of the molar amount of the phosphonic acid bis (2, 2, 2-trifluoroethyl) ester, and the feeding amount of the potassium iodide is 2%-3% of the mass of the phosphonic acid bis (2, 2, 2-trifluoroethyl) ester.

5. The scratch and impact resistant cover glass of claim 2, wherein: The feeding ratio of the nano titanium dioxide, absolute isopropyl alcohol, 2- (acryloyloxy) ethyl phosphonic acid bis (2, 2, 2-trifluoroethyl) ester is 10-20 g: 127-382 mL: 0.8-2.4 g, and the feeding amount of the γ- (methacryloyloxy) propyl trimethoxysilane is 0.5%-0.8% of the mass of the nano titanium dioxide.

6. The scratch and impact resistant cover glass of claim 2, wherein: The feeding ratio of the (9CI)-2, 4, 8, 10-tetraoxaspiro [5.5] undecane-3, 9-dipropionic acid, 2-[[4- (2-propen-1-oxyl) phenoxy] methyl] -oxirane and absolute toluene is 20-50 g: 35-92 g: 150-200 mL, the feeding amount of the triethylamine is 3%-5% of the molar amount of the (9CI)-2, 4, 8, 10-tetraoxaspiro [5.5] undecane-3, 9-dipropionic acid, and the feeding amount of the tetrabutylammonium bromide is 0.8%-1.2% of the total mass of the reactants.

7. The scratch resistant impact resistant cover glass according to claim 1, wherein: The weight average molecular weight of the aliphatic polyurethane acrylate is 1000-15000 g / mol.

8. The scratch and impact resistant cover glass of claim 1, wherein: The photoinitiator is selected from at least one of benzoyl peroxide, dicumyl peroxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone.

9. The scratch and impact resistant cover glass of claim 1, wherein: The auxiliary agent is selected from at least one of BYK-3455, BYK-3550, BYK052N, BYK-061, BYK-065.

10. A method of producing the scratch- and impact-resistant cover glass according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: (1) The aliphatic polyurethane acrylate, spiro ring type propylene monomer, modified titanium dioxide, diethyl ether, ethanol, photoinitiator and auxiliary agent are mixed according to the mass fraction, and are mechanically stirred at a speed of 300-500 rpm under light-proof conditions for 30-60 min to obtain a uniform and transparent coating solution; (2) The coating solution is coated on the surface of a clean glass body by spin coating or slot coating, the coating thickness is 10-50 μm, and then part of the solvent is volatilized by standing in an oven at 40-60 ℃ for 3-5 min; (3) transferring the glass body pre-solidified in step (2) to an ultraviolet light curing device, irradiating the surface coating with ultraviolet light with a wavelength of 365 nm and an intensity of 800-1200 mW / cm 2 for 10-30 s to completely cross-link and solidify the surface coating, thereby obtaining the scratch-resistant and impact-resistant cover plate glass.